TI_GERICHTE 16.2006.37 vom 13. Juli 2006 , rigetto provvisorio - tempestività del ricorso - redazione in lingua tedesca - TI Tribunale d'appello (2006)
rigetto provvisorio - tempestività del ricorso - redazione in lingua tedesca